Relationship Between Stress Levels and Functional Constipation Incidence in Adolescents in Surakarta - Aditya, Aisya Fikritama; Putri, Amanda Rizma Devyka; Rokhayati, Evi; Wulandari, Agustina (Journal of Maternal and Child Health, 2025)
Background: Adolescence is a time when physical and mental changes occur. They experience various mental pressures and can affect digestive health. One of the common digestive problems in adolescents is constipation. Constipation is a condition of bowel movement disorders characterized by infrequent or less than three times a week defecation or painful defecation due to hard or large-caliber feces. The purpose of this study was to determine the relationship between stress levels and functional constipation incidence among 10th grade adolescents at SMA Negeri 1 Surakarta.              Subjects and Method: This was a cross-sectional study conducted at SMA Negeri 1 Surakarta. A total of 308 students of Class X selected with the conseutive sampling method. The dependent variable was constipation. The independent variables was stress levels. Te data were collected by questionairre. The sample results of the study were analyzed using SPSS software using univariate tests and chi-square bivariate tests. Results: The incidence of stress level did not have a significant relationship to the incidence of functional constipation in adolescents (OR= 0.77; 95% CI = 0.25 to 2.37; p = 0.551). Conclusion: There is no relationship between stress levels and functional constipation incidence in adolescents in Surakarta.